An Analysis of Kurdish EFL Basic Teachers’ Needs for Designing an Effective In-service Teacher Training Course - Kheder, Lecturer: Rasool Mohammed; Hassan, Asst. Prof. Dr. Zana M. (Sulaimani Journal for Humanities, 2023)
The current paper is an extract from a PhD dissertation, which investigates the impact of teacher training courses on EFL in-service teachers. It attempts to identify the capacity development (background to teaching and classroom methodology) and subject-related needs of English as a foreign language - basic school Kurdish teachers (EFL-BKTs). Their skills, knowledge and beliefs about the two mentioned major areas are identified for the purpose of developing an in-service teacher training (INSETT) course. The current case study employs a convergent parallel design through utilising a mixed-method (quantitative and qualitative) approach. For scrutinizing the teachers’ needs, various data collection instruments including a questionnaire, semi-structured interviews, a focus group discussion and lesson observation tools are utilised. A total number of twelve participants (six EFL-BKTs, three English supervisors and three headteachers) have participated in the study. The findings of the study revealed that most of the EFL-BKTs’ needs are centred around capacity development and there are only some limited areas of subject-related issues that need to be improved through taking part in the prospective INSETT course.
Keywords: Inservice Teacher Training (INSETT); Continuing Professional Development (CPD); English as a Foreign LanguageBasic school Kurdish Teachers (EFLBKTs)